2019
DOI: 10.3390/polym11071094
|View full text |Cite
|
Sign up to set email alerts
|

FDM 3D Printing of Polymers Containing Natural Fillers: A Review of their Mechanical Properties

Abstract: As biodegradable thermoplastics are more and more penetrating the market of filaments for fused deposition modeling (FDM) 3D printing, fillers in the form of natural fibers are convenient: They have the clear advantage of reducing cost, yet retaining the filament biodegradability characteristics. In plastics that are processed through standard techniques (e.g., extrusion or injection molding), natural fibers have a mild reinforcing function, improving stiffness and strength, it is thus interesting to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
351
0
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 470 publications
(371 citation statements)
references
References 75 publications
(230 reference statements)
6
351
0
14
Order By: Relevance
“…This result would be of great interest for carrying out simulations of the structural behaviour of 3D printed parts. Recently, Mazzanti et al [40] concluded there is no recognised international standard governing the characterisation of the tensile, compressive or flexural properties of 3D-printed materials. The current standards are those used for the characterisation of bulk polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
“…This result would be of great interest for carrying out simulations of the structural behaviour of 3D printed parts. Recently, Mazzanti et al [40] concluded there is no recognised international standard governing the characterisation of the tensile, compressive or flexural properties of 3D-printed materials. The current standards are those used for the characterisation of bulk polymeric materials.…”
Section: Resultsmentioning
confidence: 99%
“…From all the research and review made on 3D printed natural fiber composites, it can be commonly seen that the surface of the 3D printed composite contains gap, cracks, and pores. is pore, crack, and gap formation is considered as limitation in many of the research and review related to 3D printing of the fiber-reinforced composites [29]. e same characteristics was observed even in the 3D printed synthetic fiber composites [30].…”
Section: Recent Trends In Additive Manufacturing Of Nfrcsmentioning
confidence: 99%
“…Process parameters (nozzle diameter, filament diameter, printing speed, melting temperature, infill geometry, infill thickness, number of layers, and thickness of layers), product parameters (fiber geometry, fiber content, treatment of fiber, and fiber morphology), and environmental conditions like humidity of the fiber will be responsible for the mechanical and acoustical properties of the panel. Recent review article by Mazzanti et al covered the product and process parameters that influences the mechanical properties of the 3D printed NFRC [29], whereas effect of product and process parameters on the acoustical properties of the 3D printed NFRC has to be investigated further. However, review article by Mamtaz et al covered some of the properties like the fiber size, bulk density of the fiber, and sample layer thickness in order to obtain optimum acoustic absorption especially at lower frequency spectrums [150].…”
Section: Additive Manufacturing Processmentioning
confidence: 99%
“…Their results show that the mechanical properties of acrylonitrile-butadiene-styrene (ABS) and poly (lactic acid) (PLA) cannot benefit from biofillers, while polyolefins have become more performant. Moreover, it is likely that better quality biocomposite printing might be obtained with specifically designed printing machines [18].…”
Section: Introductionmentioning
confidence: 99%